2020
DOI: 10.1016/j.adro.2020.04.035
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative 3-Dimensional Photographic Assessment of Breast Cosmesis After Whole Breast Irradiation for Early Stage Breast Cancer: A Secondary Analysis of a Randomized Clinical Trial

Abstract: Purpose Our purpose was to use 3-dimensional (3D) surface photography to quantitatively measure breast cosmesis within the framework of a randomized clinical trial of conventionally fractionated (CF) and hypofractionated (HF) whole breast irradiation (WBI); to identify how 3D measurements are associated with patient- and physician-reported cosmesis; and to determine whether objective measures of breast symmetry varied by WBI treatment arm or transforming growth factor β 1 ( TGFβ1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…The distance from SN-to-LVP provides a measure of vertical positional symmetry. Prior studies using two-dimensional (2D) images 7 and 3D images 27 have shown vertical positional symmetry, and not horizontal positional symmetry, to be correlated with patient-reported breast cosmesis. Therefore, in this study, we utilized vertical positional symmetry, referred to as positional symmetry, henceforth.…”
Section: Methodsmentioning
confidence: 99%
“…The distance from SN-to-LVP provides a measure of vertical positional symmetry. Prior studies using two-dimensional (2D) images 7 and 3D images 27 have shown vertical positional symmetry, and not horizontal positional symmetry, to be correlated with patient-reported breast cosmesis. Therefore, in this study, we utilized vertical positional symmetry, referred to as positional symmetry, henceforth.…”
Section: Methodsmentioning
confidence: 99%
“…Signs of breast lymphoedema were quantified using multiple tools and approaches (Table 1 ). Breast tissue dermal thickness was measured using ultrasound ( n = 12) [ 21 24 , 35 , 36 , 54 , 57 60 , 72 ] and mammography ( n = 3) [ 26 28 ]; local tissue water was measured using tissue dielectric constant (TDC) ( n = 8) [ 19 , 20 , 51 53 , 59 , 61 , 73 ]; breast volume was measured using three-dimensional surface imagery (3D-SI: n = 4) [ 37 , 40 , 56 , 63 ], magnetic resonance imaging (MRI: n = 1) [ 41 ] and anthropomorphic techniques ( n = 1) [ 36 ]; extracellular fluid volume was measured using bioimpedance spectroscopy (BIS: n = 3) [ 54 , 62 , 74 ]; tissue resistance was measured using tonometry ( n = 3) [ 55 , 59 , 62 ], the pitting test ( n = 2) [ 59 , 61 ] and indentation force ( n = 1) [ 52 ]; and dermal backflow/compensatory drainage pathways was visualised with indocyanine green imaging (ICG: n = 1) [ 73 ]. Additionally, clinician rating scales ( n = 8) [ 29 , 31 , 33 35 , 37 , 47 , 72 ] were used to identify presence of changes to the appearance, size or texture of the breast tissue.…”
Section: Resultsmentioning
confidence: 99%
“…Seven randomised controlled trials were included and assessed using the RoB 2 tool [ 18 ] (Table 1 ) [ 39 , 40 , 46 , 51 , 53 , 54 , 56 ]. Three RCTs had low overall risk of bias [ 46 , 53 , 54 ], and four were rated as having some concerns [ 39 , 40 , 51 , 56 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations